Barriers to innovation in SMEs: Can the internationalization of R&D mitigate their effects? - Rajnish Tiwari; Stephan Buse (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2007)
Technological advancements, especially in Information and Communication Technologies (ICT) have enhanced greatly the competition spurred by the globalization of the world economies. Even small and medium-sized enterprises (SMEs) are no more immune to the challenges that the globalization brings about. It is a remarkable, and in certain instances worrisome, situation since SMEs play a key-role in most economies, in that they constitute the largest business block and provide the bulk of employment. However, opportunities presented by the globalization and the entwined, simultaneous pressure to innovate opens for SMEs new arenas to engage in what we may call are global innovation activities so as to gain, retain, and further strengthen the competitive position. This pressure to go for global innovation is enhanced by given socio-demographic factors, e.g. shortage of skilled labour, in many industrialized countries. This paper presents the findings of a survey by the authors carried out in the Metropolitan Region of Hamburg in Germany to identify barriers to innovation in selected industries and to work out solutions. The project RIS-Hamburg was initiated by the State Ministry of Economic and Labour Affairs in Hamburg and co-financed by the European Union (EU). The findings of this survey are here matched against perceived opportunities and challenges presented by global innovation.
urn:nbn:de:gbv:830-tubdok-3598
Keywords: 650; Innovation Management; Barriers to Innovation; Globalization of Innovation; Research and Development; SME; Globalization; Small and Medium-sized Enterprises (SME); Internationalization of R&D; Research &Development